How H&M make concept BUY NOW THINK LETTER, H&M’s Role in Gen Z’s Hedonic and Impulsive Buying Trends - Silvia A Chairunnisah; Joseph MJ Renwarin; M Richo Rianto; Matdio Siahaan; Djuni Thamrin; Dwi Entia; Annisa D Ambarwati; Husni F Ramadhan; Hendy Tannady (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
Gen Z values experiences over material possessions. They prefer spending on activities that offer memorable experiences, such as attending events, dining out, and travel. This preference for experiences also translates into their shopping behavior, where they seek immersive and engaging retail experiences. Explore the consumer behavior of Gen Z in Bekasi, specifically their hedonic tendencies, and to provide actionable insights for H&M's marketing strategy. By understanding the unique characteristics, preferences, and values of Gen Z in this region, H&M can tailor its offerings and marketing efforts to effectively engage this influential demographic. The method of quantitative approach with the survey results found is 149 respondents with the statistical technique used is Structural Equation Modeling Partial Least Square (SEM-PLS). Understanding the hedonistic influences driving impulsive buying among Gen Z in Bekasi allows H&M to craft targeted strategies that cater to this demographic's desires while promoting sustainability. By balancing trendiness with environmental responsibility, H&M can build lasting brand loyalty and contribute positively to the global fashion landscape. This paper provides a roadmap for H&M to navigate the complex interplay of hedonism and sustainability, ensuring relevance and growth in the competitive market. Strategi yang dapat di lakukan oleh perusahaan adalah mempertahankan sifat tiba-tiba activities dari konsumen gen z seperyi embience store penataan new collection seasoning untuk tetap mempertahankan ketertarikan terhadap koleksi brand H&M. Kemudian pada dimensi Leisure Activities indikator yang memberikan pengaruh paling rendah friends opinion, strategi yang dapat dilakukan oleh perusahaan adalah meng improve pola konsumtif individu menjadji group, denga melakukan penawaran, buy 2 get 1 free atau spend 400k get 50% off. This study significantly contributes to the analysis of the influence of hedonic variables on impulsive buying behavior concerning the H&M brand. By examining the psychological and social factors that drive Gen Z in Bekasi towards impulsive purchases, this research provides valuable insights and ongoing suggestions for H&M's managerial strategies. It emphasizes the importance of balancing the "Buy Now, Think Later" concept with sustainable practices to foster long-term brand loyalty and environmental responsibility.